Intraregional trade and desindustrialization in Latin America and the Caribbean in the face of China’s irruption, 1990-2023 - Cruz Romero, Miguel Angel (Latin American Journal of Trade Policy, 2025)
The objective of this research is to examine intraregional trade in Latin America and the Caribbean, along with its commercial ties with China and the degree of export concentration/diversification by destination in both cases. Additionally, it seeks to quantify the process of deindustrialization in the region. To achieve this, the study employs the following indices: trade introversion, the Herfindahl-Hirschman index, the share of manufacturing value added in GDP, the share of manufacturing employment in total employment, the penetration of manufactured imports, and net external dependence. The central hypothesis posits that, during the analyzed period (1990–2023), the process of intraregional integration in Latin America and the Caribbean has experienced a clear decline. This phenomenon stands in stark contrast to China's growing commercial prominence in the region, whose expansion has been significant. Furthermore, the persistence of an export pattern characterized by high geographic concentration and limited market diversification is observed. Additionally, the analysis reveals an upward trend in regional deindustrialization indicators, completing a broader picture of structural transformations in the region's economy.